2006
DOI: 10.1039/b608297a
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, structures, and magnetic characterization of dicyanometalate(ii) building blocks: [NEt4][(Tp*)MII(CN)2] [MII= Cr, Co, Ni; Tp* = hydridotris(3,5-dimethylpyrazol-1-yl)borate]

Abstract: The syntheses and structures of three dicyanometalate(II) complexes, [NEt(4)][(Tp*)M(II)(CN)(2)].nMeCN.(1/2)Et(2)O (M(II) = Cr, 1, n = (1/2); Co, 2, n = 1; Ni, 3, n = 1) are described; magnetic studies indicate that 3 is diamagnetic while 1 and 2 are paramagnetic high- and low-spin S = 2 and (1/2) complexes, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…2097 cm –1 ), a feature that is attributed to the increased M→L back‐donation in the Co III complex than in the Co II species. These values for the CN stretching in 1 – 4 agree with other values from the literature for cyanide groups terminally bound to cobalt(III) and cobalt(II) centers2628 and support their monodentate coordination. Finally, the occurrence of peaks at 3381 and 3253 cm –1 [ν as (NH 2 ) and ν s (NH 2 )] for 1 and 3384 and 3283 cm –1 [ν as (NH 2 ) and ν s (NH 2 )] for 2 is indicative of the presence of the en ( 1 ) and ampy ( 2 ) ligands.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…2097 cm –1 ), a feature that is attributed to the increased M→L back‐donation in the Co III complex than in the Co II species. These values for the CN stretching in 1 – 4 agree with other values from the literature for cyanide groups terminally bound to cobalt(III) and cobalt(II) centers2628 and support their monodentate coordination. Finally, the occurrence of peaks at 3381 and 3253 cm –1 [ν as (NH 2 ) and ν s (NH 2 )] for 1 and 3384 and 3283 cm –1 [ν as (NH 2 ) and ν s (NH 2 )] for 2 is indicative of the presence of the en ( 1 ) and ampy ( 2 ) ligands.…”
Section: Resultssupporting
confidence: 88%
“…In this respect, examples of six‐coordinate cobalt(III) species of formula [CoL(CN) 3 ] (L = tridentate nitrogen donor) have been prepared,24 and the use of some of them as ligands for hydrated 3d cations has afforded high‐nuclearity cubic cages 25. In addition, only three examples of cyanide derivatives of five‐coordinate low‐spin Co II complexes are known, namely, [Co(Tp*)(CN) 2 ] – [Tp* = hydridotris(3,5‐dimethylpyrazol‐1‐yl)borate],26 [Co(triphos)(CN) 2 ] [triphos = 1,1,1‐tris(diphenylphosphinomethyl)ethane],27 and [Co(py)(CN) 4 ] 2– (py = pyridine) 28…”
Section: Introductionmentioning
confidence: 99%
“…The other geometric parameters associated with the cyanide ligands are also as expected (Ray et al, 2008). The Ni-C distances in (I) are also similar to those found in a five-coordinate Ni complex with a cis-[Ni(CN) 2 N 3 ] coordination set (Li et al, 2006), but are significantly shorter than those found for a six-coordinate Ni compound with cis-[Ni(CN) 2 N 4 ] coordination (Jiang et al, 2005). The Ni-N bonds to the chelating pdpm ligand [1.902 (2) and 1.909 (3) Å ] are longer than the Ni-C bonds, but similar to the value of 1.923 (2) Å found for the square- , 1992).…”
Section: Commentsupporting
confidence: 74%
“…Our motivation for this study is based upon the widespread utility of terminal cyanide complexes in the assembly of molecular, cyanide-bridged clusters via the "building block approach." 51,52,55- 57 Cyanide complexes with terminal cyanide ligands or open binding sites are often used as capping or blocking groups in the construction of these species. Thus, the reaction of green [Ni(L iPr )(CN)] 2with a four-coordinate, trigonal pyramidal Co(II) complex of the same ligand, [Co(L iPr )] -, 26 immediately produces a reddish-violet solution.…”
Section: Formation Of a Heterobimetallic Complexmentioning
confidence: 99%